2020
DOI: 10.15537/smj.2020.3.24910
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression and fatigue on relapsing remitting multiple sclerosis in Kingdom of Saudi Arabia

Abstract: To determine relationship between fatigue, depression with the registration in multiple sclerosis (MS) society activity, and stress with the risk developing a new attack in patients with Relapsing remitting MS (RRMS) in the Kingdom of Saudi Arabia (KSA). Methods: This was a cohort retrospective study conducted in the KSA between July 2018 and July 2019 which included a total of 465 RRMS patients. Data were collected during interviews using the Beck Depression Inventory (BDI) and Modified Fatigue Impacts Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One such disease is multiple sclerosis (MS), an autoimmune demyelinating inflammatory disorder of the CNS (12), affecting over 2.8 million people worldwide in a 2:1 female to male ratio (13). Patients with MS are predominantly treated with immunomodulatory/immunosuppressive disease-modifying therapies (DMTs), which alter the immune response, potentially increasing the risk of infection (9,14).…”
Section: Introductionmentioning
confidence: 99%
“…One such disease is multiple sclerosis (MS), an autoimmune demyelinating inflammatory disorder of the CNS (12), affecting over 2.8 million people worldwide in a 2:1 female to male ratio (13). Patients with MS are predominantly treated with immunomodulatory/immunosuppressive disease-modifying therapies (DMTs), which alter the immune response, potentially increasing the risk of infection (9,14).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies attempted to address the correlation between MS and depression [ 10 ]. In Saudi Arabia, there is limited current literature about the incidence and relationship between depression and MS [ 18 - 19 ]. In a meta-analysis conducted by Etemadifar et al, there is limited availability of data with varied quality scores, diagnostic criteria, sample size, and methods [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Several pre-pandemic studies in the KSA found greater levels of depression, along with significant impacts on quality of life, among MS sufferers. [7][8][9][10][11] Compared with age-matched healthy individuals and persons with other chronic illnesses, PwMS had higher levels of anxiety and depression. 12 Acute stress is also associated with relapses in PwMS.…”
mentioning
confidence: 99%
“… 6 Several pre-pandemic studies in the KSA found greater levels of depression, along with significant impacts on quality of life, among MS sufferers. 7 11 …”
mentioning
confidence: 99%